2020
DOI: 10.1108/qram-11-2019-0122
|View full text |Cite
|
Sign up to set email alerts
|

Data analytics by management accountants

Abstract: Purpose This paper aims to understand how the tasks of management accountants (MA) are affected by data analytics (DA). Design/methodology/approach A qualitative methodology was deemed most appropriate given the exploratory nature of the research questions (RQ). In total, 10 open-ended interview questions were used to gather the evidence. The case study design was inductive, yielding rich data from 29 respondents representing 20 different organizations. Findings Answers were provided to three interrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
0
16
1
7
Order By: Relevance
“…We focus on management accountants’ skills because they are generally known to play an important role as information providers to top managers in the decision-making process (Ahrens, 1997; Burns et al , 2013; Erhart et al , 2017; Hiller et al , 2014; Ndemewah et al , 2019; Spraakman et al , 2020; ten Rouwelaar et al , 2018; Wolf et al , 2020; Youssef and Mahama, 2021). This role is in line with common definitions of management accounting, which see this function as “partnering in management decision making, devising planning and performance management systems, and providing expertise in financial reporting and control to assist management in the formulation and implementation of an organization’s strategy” (Institute of Management Accountants, 2008, p. 1).…”
Section: Theory Related Literature and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…We focus on management accountants’ skills because they are generally known to play an important role as information providers to top managers in the decision-making process (Ahrens, 1997; Burns et al , 2013; Erhart et al , 2017; Hiller et al , 2014; Ndemewah et al , 2019; Spraakman et al , 2020; ten Rouwelaar et al , 2018; Wolf et al , 2020; Youssef and Mahama, 2021). This role is in line with common definitions of management accounting, which see this function as “partnering in management decision making, devising planning and performance management systems, and providing expertise in financial reporting and control to assist management in the formulation and implementation of an organization’s strategy” (Institute of Management Accountants, 2008, p. 1).…”
Section: Theory Related Literature and Hypothesesmentioning
confidence: 99%
“…Recent studies on the effects of big data on management accountants have suggested that technological developments around big data may have a decisive influence on the role of management accountants, suggesting that such individuals will have to acquire new data-related skills to maintain their standing as the primary information providers to management (Andreassen, 2020; Bhatta and Hiebl, 2022; Kokina et al , 2021; Lawson, 2019; Oesterreich and Teuteberg, 2019; Spraakman et al , 2020; Schnegg and Möller, 2022; Szukits, 2022; Wadan et al , 2019; Wolf et al , 2020; Youssef and Mahama, 2021). In particular, big data and the associated new technologies are expected to lead to an elimination of repetitive tasks, which allows management accountants to spend less time on data collection and more time on data evaluation, data analysis and data interpretation (Andreassen, 2020; Lawson, 2019).…”
Section: Theory Related Literature and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey based on 20 companies from 2021 also indicates that management accountants have not taken charge of the data analytic opportunities. The companies surveyed remain largely focused on descriptive and financial data analysis rather than on more complex activities using external data, operational data and modelling (Spraakman et al, 2021). However, other researchers within the MA field are also very sceptical about the digital revolution affecting MA and decision-making (Quattrone, 2016;Vasileva, 2020), whereas others (Bhimani, 2018(Bhimani, , 2020Kaplan, 2008;Schneider et al, 2015;Warren et al, 2015) argued years ago that MA must take into account the new options and possibilities given by AI/ML.…”
Section: The Use Of External Data For Management Accountingmentioning
confidence: 99%